ANATOMI KEKERASAN MAHASISWA DI MAKASSAR - Marijan, Kacung; Fitrianto, Hari (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This study aims to unravel the cycle of student’s violence by tracing the roots of violence and describe the anatomy of student violence in Makassar. Understanding the anatomy of student’s violence can contribute in breaking the chain of student’s violence. This study uses qualitative research method. The paradigm was rooted in cultural anthropology and sociology. The paradigm is a process of investigation to understanding sosial phenomena by differentiating, comparing, cataloging, and classifying research subjects those who related with student violencein Makassar. The findings of this study indicate a violence is an act of affirmation of student identity. Source reference related to the assumption that students are agents of changes and have social and political responsibility to the country.